Perbandingan Peran Penyidik dan Penuntut Umum dalam Sistem Hukum Acara Pidana Indonesia dan Thailand: Studi Kasus tentang Penangkapan Perkara Korupsi - Evi, Safira; Irawan, Andrie (Indonesian Journal of Law and Justice, 2024)
This study discusses the differences in the definition and authority of law enforcement in the eradication of corruption in Indonesia and Thailand. In Indonesia, corruption is defined in Law No. 20 of 2001 as an act of illegally enriching oneself or others that harms the state's finances or the country's economy. This definition is broader, covering the private sector and the act of enriching oneself without having to directly harm the state's finances. In contrast, in Thailand, the Anti-Corruption Act B.E. 2546 (1999) focuses on public officials and acts that harm the state. In terms of law enforcement authority, there are similarities between the two countries, such as the duties of investigators and public prosecutors in handling corruption cases. However, the differences include aspects of filing a prosecution, where in Thailand victims can participate in filing claims, as well as differences in providing instructions and rescuing state assets, with Indonesia relying on the public prosecutor and Thailand using AMLO.